Towards an E-Psychology Solution to Support, Intervene and Educate the Control of Emotions in Infants - Alvites-Huamaní, Cleofe (2023)
Anxiety and depression in infants are a problem that is increasing, this being a consequence of the global pandemic caused by COVID-19. The current panorama indicates that infants are possible victims of suffering from these moods at very early ages and in the worst case, it becomes the leading cause of child suicide. For this reason, it is very important to seek resources and means to mitigate the situation. The current project consisted of making a web application for the control of emotions in primary school children through modules made up of theoretical sessions that cover the management of emotions, thoughts, assertiveness, frustration, breathing, and muscle relaxation. Each module in turn has an intervention session, which consists of situations that are presented to the infants with the aim of analyzing the psychological impact that the theoretical sessions had, with the main purpose of improving or intervening the control of their emotions.